A Dynamic Model of Mercury's Magnetospheric Magnetic Field. Issue 20 (21st October 2017) - Korth, Haje; Johnson, Catherine L.; Philpott, Lydia; Tsyganenko, Nikolai A.; Anderson, Brian J.
Abstract: Mercury's solar wind and interplanetary magnetic field environment is highly dynamic, and variations in these external conditions directly control the current systems and magnetic fields inside the planetary magnetosphere. We update our previous static model of Mercury's magnetic field by incorporating variations in the magnetospheric current systems, parameterized as functions of Mercury's heliocentric distance and magnetic activity. The new, dynamic model reproduces the location of the magnetopause current system as a function of systematic pressure variations encountered during Mercury's eccentric orbit, as well as the increase in the cross‐tail current intensity with increasing magnetic activity. Despite the enhancements in the external field parameterization, the residuals between the observed and modeled magnetic field inside the magnetosphere indicate that the dynamic model achieves only a modest overall improvement over the previous static model. The spatial distribution of the residuals in the magnetic field components shows substantial improvement of the model accuracy near the dayside magnetopause. Elsewhere, the large‐scale distribution of the residuals is similar to those of the static model. This result implies either that magnetic activity varies much faster than can be determined from the spacecraft's passage through the magnetosphere or that the residual fields are due to additional external current systems not represented in the model or both. Birkeland currents flowing along magnetic field lines between the magnetosphere and planetary high‐latitude regions have been identified as one such contribution. Key Points: We present a dynamic model of Mercury's magnetospheric magnetic field parameterized by heliocentric distance and magnetic activity Model reproduces the location of the magnetopause current system as a function of systematic pressure variations Model reproduces increase in the cross‐tail current intensity with increasing magnetic activity